Penentuan Fluks Neutron Termal di Fasilitas Kalibrasi Neutron dengan Menggunakan Keping Indium - Tjipta, . (Program Studi Pendidikan Fisika UHAMKA, 2015)
The purpose of this study was to determine the magnitude of the thermal neutron flux in the neutron calibration facility. Determination of the neutron flux in the neutron calibration facility has been carried out by the method of activation puck. In the measurement of thermal neutron flux distribution using Indium-116m puck as much as 17 pieces with the same distance that attaches to the front placed 80cm Ã 80cm graphite. Results of the thermal neutron flux measurement has an average of 922.1139179 n/cm2.s. Thus it can be said that the thermal neutron flux distribution in the neutron calibration facility fairly evenly with a difference of less than 5%. Key words: Neutron Flux, Thermal Neutron, Activation, Neutron Calibration.